CREM Alpha Enhances IL-21 Production in T Cells In Vivo and In Vitro - Ohl, Kim; Wiener, Anastasia; Lippe, Ralph; Schippers, Angela; Zorn, Carolin; Roth, Johannes; Wagner, Norbert; Tenbrock, Klaus (Frontiers in Immunology, 2016)
The cAMP-responsive element modulator alpha (CREMα) plays a role in autoimmunity and, in particular, in systemic lupus erythematosus. CREMα negatively regulates IL-2 transcription and activates IL-17 expression by direct transcriptional mechanisms. To understand the role of CREM in autoimmunity, we recently generated a mouse with a transgenic overexpression of CREMα selectively in T cells. This mouse is characterized by enhanced IL-17 and IL-21 expression. We, herein, dissect the transcriptional mechanisms of enhanced IL-21 transcription in these mice. T cells of CREMα transgenic mice display an enhanced binding of CREMα to the CD3ζ chain promoter resulting in decreased CD3ζ chain expression. This is accompanied by a decreased excitation threshold and enhanced Ca2+ influx, which is known to induce IL-21 expression via NFATc2 activation. However, CREMα directly binds to cAMP-response element (CRE) half-site within the Il-21 promoter, which results in enhanced promoter activity shown by promoter reporter assays. CREMα-induced IL-21 transcription is not abrogated in the presence of cyclosporine A but depends on an intact CRE site within the IL-21 promoter, which suggests that CREM largely enhances IL-21 expression by direct transcriptional regulation. IL-21 transcription is critical for IL-17 generation in these mice, since IL-21 receptor blockade downregulates IL-17 transcription to wild-type levels. Finally, this is of functional relevance since CREMα transgenic mice display enhanced disease activity in dextran sodium sulfate-induced colitis accompanied by higher local IL-21 expression. Thus, we describe two novel mechanisms of CREMα-dependent IL-21 transcription. Since T cells of systemic lupus erythematosus patients are characterized by enhanced IL-21 transcription, this might also be of functional relevance in humans.